THE EVOLUTION OF FRONTOTEMPORAL DEMENTIA DUE TO THE MAPT MUTATION: A SEVENTEEN YEAR NATURAL HISTORY STUDY. Issue 11 (9th October 2013) - Mahoney, Colin; Yeatman, T; Rohrer, JD; Manning, E; Leung, KK; Rossor, MN; Warren, JD; Fox, N
Abstract : Introduction: Frontotemporal Dementia (FTD) is a common cause of early–onset dementia. A high proportion of cases are due to autosomal dominant mutations. Understanding the natural history of these disorders will be important in the development of diagnostic biomarkers and future disease modifying therapies. However, natural history studies in FTD are lacking. Here we present longitudinal clinical, neuropsychological and neuroimaging data on two members of a family followed over 17 years. Methods: 13 assessments were carried out during follow–up. Assessments included volumetric MRI, clinical and neuropsychological assessments. Volumetric MRI underwent whole–brain and hippocampal segmentation. Consecutive whole brain and hippocampal regions underwent affine registration and volume change was calculated using the boundary shift integral. Rates of whole brain and hippocampal change were calculated. Patterns of atrophy were visualised using voxel–based morphometry. Results: Genetic testing confirmed a mutation in MAPT (exon 10+16 mutation) in one sibling who manifested symptoms 11 years after initial assessment. Neuropsychological changes were only detected one year after clinical onset with a decline in episodic memory and naming. However, increased rates of whole brain atrophy were evident as early as the ten years from onset (carrier=1.1%/year, non–carrier 0.1%). On average rates of hippocampal atrophy were disproportionate (2.9%/year) compared to whole brain atrophy (0.6%/year). Rates of atrophy had a non–linear profile. VBM analysis confirmed atrophy of bilateral anterior and medial temporal lobes. Discussion: This natural history study demonstrates that atrophy in MAPT mutations may be detectable up to a decade in advance of clinical onset. Hippocampal atrophy may be a more sensitive disease biomarker in MAPT associated FTD. Non–linear rates of atrophy may suggest disease evolution has multiple phases.